Biomechanics of highly proficient Karate practitioners during changing task - Gavagan, C. (University of the Sunshine Coast, 2021)
Karate is practised worldwide and is built on a grading system that emphasises specific criteria that need to be met to progress in rank, including the level of training and the skilful use of techniques individually or in Kumite 1-6. This standardisation of assessing skills presents an opportunity to examine the movement strategies of Karate practitioners who have been defined as experts by their discipline. The unique series of studies that constitute this thesis are based on the combined use of an Ecological Dynamic framework, performance analysis, and biomechanical analytical techniques to identify and quantify patterns, frequencies, and strategic behaviours in competitive points-sparring as well as investigating how expert Karate practitioners adapt their movements to meet changes in constraints (physical and instructional) and nested tasks.